2020
DOI: 10.1542/hpeds.2019-0284
|View full text |Cite
|
Sign up to set email alerts
|

Actively Doing Less: Deimplementation of Unnecessary Interventions in Bronchiolitis Care Across Urgent Care, Emergency Department, and Inpatient Settings

Abstract: BACKGROUND AND OBJECTIVES: Quality improvement (QI) initiatives have increased provider adherence to individual components of a bronchiolitis clinical practice guideline (CPG). Few have evaluated complete adherence to a guideline in multiple types of care settings. Our aim with this study was to increase complete adherence to our institutional bronchiolitis CPG in urgent care center, emergency department, and inpatient settings. METHODS:We conducted a QI study at a single pediatric institution with multiple ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…A 2014 systematic review 18 of 14 published QI initiatives in inpatient bronchiolitis care found that these interventions were associated with reductions in bronchodilator, steroid, antibiotic, and CR use. The QI efforts included in this review or published after the review have been associated with reduced use of nonrecommended services by implementing local clinical pathways citing AAP recommendations [19][20][21][22][23][24][25][26][27][28][29] ; international studies using other national guidelines as the basis for local improvements have been associated with similar improvements. [30][31][32][33] Such QI efforts constitute 1…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%
“…A 2014 systematic review 18 of 14 published QI initiatives in inpatient bronchiolitis care found that these interventions were associated with reductions in bronchodilator, steroid, antibiotic, and CR use. The QI efforts included in this review or published after the review have been associated with reduced use of nonrecommended services by implementing local clinical pathways citing AAP recommendations [19][20][21][22][23][24][25][26][27][28][29] ; international studies using other national guidelines as the basis for local improvements have been associated with similar improvements. [30][31][32][33] Such QI efforts constitute 1…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%
“…Standard processes and tools facilitate implementation, such as interdisciplinary teams, explicit goal setting, and frequent performance feedback. 21,22 Change management strategies promoting organizational culture change are also essential to successful implementation. 23 Our study participants reported that these elements are also important to deimplementation, with interviews highlighting the need for audit and feedback, stakeholder engagement, and building trust and respect among participants.…”
Section: Discussionmentioning
confidence: 99%
“…Similar deimplementation work has already been successfully accomplished in many fields of medicine, including pulse oximetry use for bronchiolitis management in children, imaging utilization for evaluation of low-risk headaches in acute care settings, screening criteria for cervical cancer, and numerous others. [18][19][20]…”
Section: Deimplementation: a Promising Solution To Alarm Fatiguementioning
confidence: 99%